2008
DOI: 10.1016/j.tvjl.2007.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E-cadherin, P-cadherin and β-catenin in canine malignant mammary tumours in relation to clinicopathological parameters, proliferation and survival

Abstract: Cadherin-catenin complexes play a critical role in intercellular adhesion, and their altered expression has been implicated in tumour progression. In this study, the expression of E-cadherin, P-cadherin and beta-catenin was analysed in 65 canine malignant mammary tumours and correlated with clinicopathological parameters, proliferation and survival. Reduction in E-cadherin expression was significantly associated with increased tumour size, high histological and invasion grades, lymph node metastasis and high m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
68
5
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 34 publications
(84 reference statements)
9
68
5
4
Order By: Relevance
“…39 Several studies of canine mammary tumors have reported that loss of E-cadherin, alone or in combination with loss of b-catenin, is associated with the presence of metastasis or with a shorter overall survival period. 1,5,10 Studies on E-cadherin expression in feline mammary tumors are scarce. An earlier study examining normal mammary tissue, hyperplastic lesions, and a number of neoplasms (4 adenomas and 14 carcinomas) reported that the loss of E-cadherin and abnormalities in the pattern of membranous location were associated with some of the carcinomas but not with adenomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Several studies of canine mammary tumors have reported that loss of E-cadherin, alone or in combination with loss of b-catenin, is associated with the presence of metastasis or with a shorter overall survival period. 1,5,10 Studies on E-cadherin expression in feline mammary tumors are scarce. An earlier study examining normal mammary tissue, hyperplastic lesions, and a number of neoplasms (4 adenomas and 14 carcinomas) reported that the loss of E-cadherin and abnormalities in the pattern of membranous location were associated with some of the carcinomas but not with adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…34 In the field of veterinary pathology, the loss of E-cadherin expression and the loss of its cytoplasmatic molecular anchorage, b-catenin, are well-established prognostic factors in canine mammary carcinomas. 1,5,10 However, few studies have been published on the expression of EMT markers (E-cadherin, b-catenin, or vimentin) in feline mammary carcinomas. 6,18,38 Those reports in the literature point to a high percentage of mammary carcinomas expressing vimentin as well as having a reduction of E-cadherin in the cell membranes of the neoplastic cells.…”
mentioning
confidence: 99%
“…E-cadherin is a cell adhesion protein complex widely described in the literature as a tumor suppressing agent, and loss of E-cadherin function contributes to lack of cellular differentiation and growth of the primary lesion by several potential mechanisms (Shiozaki et al, 1996;Brunetti et al, 2003;De Matos et al, 2007;Gama et al, 2007). Tegoshi et al (2000) demonstrated that E-cadherin was present in the cell membrane of normal mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies involving human and canine neoplasms have demonstrated that the expression of cadherins is altered during tumor progression (Wijnhoven et al, 2000;Menke et al, 2001;Bankfalvi et al, 2002;Gama et al, 2007;Brunetti et al, 2003;De Matos et al, 2007;Polton et al, 2007), and that more aggressive phenotypes express less E-cadherin (Torres et al, 2005;Brunetti et al, 2003;De Matos et al, 2007;Gama et al, 2007). More recent studies have shown that a decrease in E-cadherin expression or its translocation from the plasma membrane to the cytoplasm and/or nucleus can be crucial events in adherent junction destabilization (Gloushankova, 2008;Salahshor et al, 2008;Elston et al, 2009;Knirsh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The primary antibodies used were mouse monoclonal antibodies raised against E-cadherin (Clone 4A2C7, Invitrogen) and β-catenin (Clone CAT-5H10, Invitrogen), at 1:100 dilution in PBS, as previously established for canine tissues [44].…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%